1. The problem statement, all variables and given/known data Consider the following code fragment. for i=1 to n/2 do for j=i to n-i do for k=1 to j do output ‘‘foobar’’ Assume n is even. Let T(n) denote the number of times ‘foobar’ is printed as a function of n. (a) Express T(n) as three nested summations. (b) Simplify the summation. Show your work. 2. Relevant equations 3. The attempt at a solution I thin I understand a) I got: [tex]\sum (\sum (\sum output "foobar" ))[/tex] the sum bounds starting from the outside inward: i = 1 to n/2 j = 1 to n-i k = 1 to j I'm not sure how to simplify this. Could someone please explain it to me?